2021
DOI: 10.3389/fmars.2021.700687
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers in Ringed Seals Reveal Recent Onset of Borealization in the High- Compared to the Mid-Latitude Canadian Arctic

Abstract: Warming of the Arctic has resulted in environmental and ecological changes, termed borealization, leading to the northward shift of temperate species. Borealization has occurred across all trophic levels, altering the structure of the food web. The onset and rate of borealization likely varies with latitude, depending on local warming and advection of warmer water into the Arctic. In order to assess latitudinal trends in food web structure in the Arctic, we analyzed stable nitrogen isotopes of specific amino a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Like Greenland Sea harp seals, harp seals from the Northwest Atlantic therefore integrate a δ 15 N baseline influenced by both 15 N‐enriched Pacific water and 15 N‐depleted Atlantic water over the year. de la Vega et al (2021) observed an increasing decadal trend in δ 15 N Phe in ringed seals from the Canadian Arctic Archipelago and Baffin Bay, that has been explained by the increasing influence of 15 N‐enriched Pacific‐derived water in these regions, and the effect of increasing primary production and in turn benthic denitrification. The increasing trend in δ 15 N Phe in ringed seals from the Baffin Bay was less pronounced than in the Canadian Arctic Archipelago, likely reflecting a dilution effect of the Pacific water influence when reaching southern Baffin Bay (de la Vega et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Like Greenland Sea harp seals, harp seals from the Northwest Atlantic therefore integrate a δ 15 N baseline influenced by both 15 N‐enriched Pacific water and 15 N‐depleted Atlantic water over the year. de la Vega et al (2021) observed an increasing decadal trend in δ 15 N Phe in ringed seals from the Canadian Arctic Archipelago and Baffin Bay, that has been explained by the increasing influence of 15 N‐enriched Pacific‐derived water in these regions, and the effect of increasing primary production and in turn benthic denitrification. The increasing trend in δ 15 N Phe in ringed seals from the Baffin Bay was less pronounced than in the Canadian Arctic Archipelago, likely reflecting a dilution effect of the Pacific water influence when reaching southern Baffin Bay (de la Vega et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…de la Vega et al (2021) observed an increasing decadal trend in δ 15 N Phe in ringed seals from the Canadian Arctic Archipelago and Baffin Bay, that has been explained by the increasing influence of 15 N‐enriched Pacific‐derived water in these regions, and the effect of increasing primary production and in turn benthic denitrification. The increasing trend in δ 15 N Phe in ringed seals from the Baffin Bay was less pronounced than in the Canadian Arctic Archipelago, likely reflecting a dilution effect of the Pacific water influence when reaching southern Baffin Bay (de la Vega et al, 2021). Here, the absence of trend in δ 15 N Phe in harp seals from the Northwest Atlantic population could result from the increased influence of both 15 N‐enriched Pacific water and 15 N‐depleted Atlantic water, counterbalancing each other in the migration area of this population.…”
Section: Discussionmentioning
confidence: 99%
“…These environmental effects lead to changes in the ecosystems, which mainly include increased generalization of the food webs, higher primary production, and inflow of boreal species into the Arctic marine ecosystems [ 3 5 , 7 11 , 16 , 18 , 19 ]. The retrospective SIA studies from the Arctic and North Atlantic to date use basal (= filter feeders) and top (= marine mammal top predators) food web components [ 21 , 22 , 31 , 32 , 34 41 , 43 , 44 ]. Shifts in their trophic ecology, which would coincide in time with the mentioned increased environmental impact of climate change since the late 1990s/early 2000s, were only evident in narwhals and ringed seals from East and West Greenland [ 21 , 22 , 31 , 32 , 34 41 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The retrospective SIA studies from the Arctic and North Atlantic to date use basal (= filter feeders) and top (= marine mammal top predators) food web components [ 21 , 22 , 31 , 32 , 34 41 , 43 , 44 ]. Shifts in their trophic ecology, which would coincide in time with the mentioned increased environmental impact of climate change since the late 1990s/early 2000s, were only evident in narwhals and ringed seals from East and West Greenland [ 21 , 22 , 31 , 32 , 34 41 , 43 , 44 ]. Ontogenetic changes and different timing of temporal changes in trophic ecology, however, were often found [ 21 , 22 , 31 , 32 , 34 41 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation